(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article explores “Myshyk Mazar” as an ethnographic object, analyzing its historical, cultural, and religious significance. The study employs methods of oral history documentation and comparative analysis to investigate the origins of the mazar’s name, its historical importance, and its role in community life. The rituals conducted at the shrine are examined as examples of the synthesis of Islamic and ancient beliefs. The structure of these rituals, their symbolic meanings, and their social functions are elaborated upon. The findings emphasize the importance of sacred sites for ethnographic and cultural studies while contributing new data to the ethnography of Kyrgyzstan.